2021
DOI: 10.3390/cryst11010065
|View full text |Cite
|
Sign up to set email alerts
|

Textures of Nematic Liquid Crystal Cylindric-Section Droplets Confined by Chemically Patterned Surfaces

Abstract: The director fields adopted by nematic liquid crystals (LCs) that are confined by the surface to form long, thin droplets are investigated using polarising optical microscopy. Samples are produced by de-wetting of the LC on a surface patterned with alternating high-surface energy and low-surface energy stripes of 10–30 μm width. The droplets obtained are expected to adopt a profile which is that of a longitudinal section of a cylinder and, as this suggests, the director fields observed are variants in the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 53 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…It may simply be that (within the confines of the droplet) this is the thermodynamically favoured way for these domains to be matched up with each other. Arguments of this kind have been used to explain another example of alternating defects; the alternation of radial and hyperbolic defects in escaped radial director fields of nematic LCs [21,43]. An alternative approach to the problem is to treat these features as paramorphotic; to argue that they are produced because the development of strain at the isotropic to columnar transition results in buckling of the columns.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It may simply be that (within the confines of the droplet) this is the thermodynamically favoured way for these domains to be matched up with each other. Arguments of this kind have been used to explain another example of alternating defects; the alternation of radial and hyperbolic defects in escaped radial director fields of nematic LCs [21,43]. An alternative approach to the problem is to treat these features as paramorphotic; to argue that they are produced because the development of strain at the isotropic to columnar transition results in buckling of the columns.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a previous study of columnar discotic LCs using stripes ~10 μm wide we found droplet profiles that approached those of a hemi-cylinder (Figure 4(a), contact angles approaching 90°) [22] but in more recent studies of calamitic nematic LCs on stripes ~20 μm wide we have found very low contact angles (~10°); much more shallow longitudinal sections of a cylinder. (Figure 4(b)) [21].…”
Section: Optical Textures Observed For De-wetted Stripesmentioning
confidence: 99%
See 3 more Smart Citations